Naturalistic inquiries of M. Bashkirtseva as an artist: synthesis of literature and art - Dorohan, Ilona V.; Boiko, Olha S.; Kyrylenko, Kateryna M.; Oborska, Svitlana V.; Shandrenko, Olha M. (Linguistics and Culture Review, 2021)
The study pioneers the naturalistic search of Bashkirtseva as an artist, which was expressed in her involvement in the creation of a new movement in art, including painting, defined as naturalism. Several aesthetically significant and self-sufficient stages of its development in the creative activity of Maria Bashkirtseva are presented. It is noted that in this process the noblewoman's high education at home with her interest in the interaction of literature and painting, which in due course was understood as aesthetically valuable for painting and the artist, was initially obtained. The importance of the next naturalistic stage of Bashkirtseva is underlined, which is conditioned by her rapid acquisition of the European urban culture, one of the specific features of naturalism, first of all, the French one with the priority of Parisian peculiarities. In this way, it is emphasized that Bashkirtseva was not only focused on the development of critical and pictorial-literary trends in naturalism but also involved in their creation, developing the synthesis of literature and painting. It is emphasized that Bashkirtseva in the mastery of Dostoevsky largely anticipated the concept of Bakhtin, “following” the images of the Russian classic, giving them their naturalistic meaning.